Point-to-point quantum key distribution resistant to fake-state attacks - I. S. Sushchev (APL Quantum)
We propose a novel point-to-point quantum key distribution protocol based on the states from a great circle of the Bloch sphere that maintains the simplicity of the widely used BB84 protocol while offering enhanced resilience against fake-state attacks. Our approach leverages an infinite set of bases, reducing the probability of successful eavesdropping through basis-matching strategies. We derive the security of the protocol against collective attacks, provide an estimation of secret key length, and outline its resistance to common fake-state attack techniques, such as detector blinding. We also use entropic uncertainty relations to set the lower bound on Eve’s conditional entropy. Furthermore, we explore the realistic eavesdropping scenario considering finite-precision state preparation and discuss potential implementation strategies for our protocol considering finite resources and noise affection.